Feast or flee: government payments and labor migration from agriculture in the United States - D’Antoni, Jeremy; Mishra, Ashok K.; Barkley, Andrew P. (My University, 2012)
Government payments have been a part of agriculture since 1933 and at no time has the government stated a policy objective of decreasing the agricultural labor force. The reality of the matter may be considerably different. Using time series data and new econometric techniques, this study finds agricultural policy may have an unintended impact on labor migration. Specifically, we find that government payments increased labor migration from the farm. From 1939 to 2007, increased direct government payments resulted in greater migration of labor from agriculture. Government policy appears to have shown limited success at sustaining the agricultural labor force.
Keywords: Labor migration; Agricultural policy; Direct government payments; Farm income; Farm households; Time-series analysis